Impact assessment of Integrated Pest Management modules validated for Brinjal, Paddy, Pigeon pea and Cauliflower - Niranjan Das; B.P. Giri; A.B. Das (Journal of Agricultural Extension Management, 2025)
Impact assessment of IPM modules validated by KVK, Boudh, Odisha during 2009-2012 revealed that the technologies are being adopted by the farmers at variable rate over time. The highest adoption rate (45%) was observed in /PM module for management of fruit and shoot borer infestation in brinjal, with horizontal expansion of 115 ha additional area over four years. Lower adoption rate (20%) was observed for the /PM module for management of pod borer in pigeon pea. The /PM modules for management of stem borer in paddy and tobacco caterpillar in cauliflower were adopted by 25% and 30% respondents respectively. Among the biological constraints, non-availability of pheromone trap, lure and bio agents rank first with frequency of 80% followed by delay/difficulty in input availability (76%). The other deterrents observed under this category are non-availability of neem oil/cake, inadequate supply and poor quality of inputs. Among technological impediments are non-availability of skilled labour which ranks first (75%) followed by lack of trained extension personnel for follow-up action. High cost of labour is the major socio economic constraint (90%) followed by lack of credit facility (82%) for adoption of these technologies. For successful adoption of these modules in a sustainable manner it is essential to address these constraints in a time bound manner and system paradigm mode.